2012
DOI: 10.1088/0967-3334/33/3/395
|View full text |Cite
|
Sign up to set email alerts
|

Linear and nonlinear tremor acceleration characteristics in patients with Parkinson's disease

Abstract: The purpose of the study was to evaluate linear and nonlinear tremor characteristics of the hand in patients with Parkinson's disease (PD) and to compare the results with those of healthy old and young control subjects. Furthermore, the aim was to study correlation between tremor characteristics and clinical signs. A variety of nonlinear (sample entropy, cross-sample entropy, recurrence rate, determinism and correlation dimension) and linear (amplitude, spectral peak frequency and total power, and coherence) h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 37 publications
(74 reference statements)
2
38
0
5
Order By: Relevance
“…like the ones proposed in this study have been shown to correlate with the UPDRS tremor scores during routine non-surgical clinical evaluation [20].…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…like the ones proposed in this study have been shown to correlate with the UPDRS tremor scores during routine non-surgical clinical evaluation [20].…”
Section: Discussionsupporting
confidence: 66%
“…Gravity also has an effect on the data measured by the accelerometer [30] and therefore has to be corrected for before any outcome measures are extracted. In contrast to previously proposed methods, in which the effect of gravity was not suppressed, our method uses a cutoff frequency of 2 Hz for the smoothness-priors detrending method which has been shown to suppress the effect of gravitational acceleration on the raw data [20]. With regard to the outcome measures, as Papapetropoulos et al [27] used a commercial system; they were restricted to the outcome measures available from it, i.e., tremor intensity, center frequency, its standard deviation, and harmonic index.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Для реализации поставленной цели применена накожная неинвазивная электромио-графия (ЭМГ) с новыми нелинейными и традиционными линейными параметрами сигнала [4,16,17].…”
Section: характеристика исследованияunclassified